MANAJEMEN MODERN SEBAGAI BASIS PENGEMBANGAN KELEMBAGAAN ISLAM IDEAL - Moch Bachrurrosyady Amrulloh (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2019)
Abstracts: Management is one of the main points of the study in the following discussion. Given the institutional development cannot be separated from management studies. In this discussion we will explore a number of studies related to general and specific management concepts, the difference between management as an art and as a science, leadership in management, management functions as an institutional deve-lopment, management principles as a basis for institutional development and will also be discussed about Abraham's needs theory Maslow In conclusion, it can be seen that indicators of the success of an institution can be seen through the continuity of management functions, namely planning, organizing, commanding, coordinating, to the controlling stage. Continuity between the four functions is very important because without one of these functions the purpose of an organization will not be achieved effectively and efficiently.Keywords: Management, Institutional, Islamic Institution